2022
DOI: 10.1155/2022/8741787
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols Targeting Oxidative Stress in Spinal Cord Injury: Current Status and Future Vision

Abstract: A spinal cord injury (SCI) occurs when the spinal cord is deteriorated or traumatized, leading to motor and sensory functions lost even totally or partially. An imbalance within the generation of reactive oxygen species and antioxidant defense levels results in oxidative stress (OS) and neuroinflammation. After SCI, OS and occurring pathways of inflammations are significant strenuous drivers of cross-linked dysregulated pathways. It emphasizes the significance of multitarget therapy in combating SCI consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 265 publications
1
4
0
Order By: Relevance
“…Recent studies have shown that oxidative stress is involved in a series of neurological diseases, including cerebral ischemia, SCI, and Alzheimer’s disease. Many studies have confirmed that excessive ROS can exacerbate SCI . Excessive ROS production can cause severe damage to proteins and DNA in spinal cord tissue, ultimately leading to increased inflammation and neuronal cell death. , ROS, GSH, SOD, and MDA are widely used as markers of oxidative stress after SCI. , In the present study, both in vitro and in vivo experiments showed that SeNPs-Met-MVs could be a key regulator of neuroprotection in response to oxidative stress. It was confirmed by immunofluorescence experiments that SeNPs-Met-MVs could reduce the expression of the HIF-1α, regulate the hypoxic environment, and are a key regulator of neuroprotection in response to oxidative stress.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Recent studies have shown that oxidative stress is involved in a series of neurological diseases, including cerebral ischemia, SCI, and Alzheimer’s disease. Many studies have confirmed that excessive ROS can exacerbate SCI . Excessive ROS production can cause severe damage to proteins and DNA in spinal cord tissue, ultimately leading to increased inflammation and neuronal cell death. , ROS, GSH, SOD, and MDA are widely used as markers of oxidative stress after SCI. , In the present study, both in vitro and in vivo experiments showed that SeNPs-Met-MVs could be a key regulator of neuroprotection in response to oxidative stress. It was confirmed by immunofluorescence experiments that SeNPs-Met-MVs could reduce the expression of the HIF-1α, regulate the hypoxic environment, and are a key regulator of neuroprotection in response to oxidative stress.…”
Section: Discussionsupporting
confidence: 52%
“…46 Excessive ROS production can cause severe damage to proteins and DNA in spinal cord tissue, ultimately leading to increased inflammation and neuronal cell death. 47,48 ROS, GSH, SOD, and MDA are widely used as markers of oxidative stress after SCI. 49,50 In the present study, both in vitro and in vivo experiments showed that SeNPs-Met-MVs could be a key regulator of neuroprotection in response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…High-performance liquid chromatography in conjunction with photodiode array detection, electrospray ionization-mass spectrometry, and phytochemical fingerprinting of JSK was used. Additionally, JSK seems to target several pathways (biochemical and cellular) to promote functional recovery and enhance the results of SCI ( Su et al, 2013 ; Islam et al, 2022 ). To evaluate the therapeutic effects of ethanolic extract of Mucuna pruriens (MP) in treating SCI, Chandran et al used the widely researched standardized Multicenter Animal Spinal Cord Injury Study animal model of the contusive spinal cord.…”
Section: Phytoconstituents In Different Neurological Disordersmentioning
confidence: 99%
“…Traumatic spinal cord injury (SCI) causes acute mechanical contusion of neural tissue and induces prominent neuroinflammation, a characteristic that is evident in brain injury and other acute neurological diseases 1,2 . Neuroinflammation and oxidative stress (OS) following SCI trigger secondary neuropathies such as glial accumulation, neuronal loss, and demyelination that exacerbate neurological dysfunction and functional disorder 3–5 . Microglia are the resident immune cell of the central nervous system and become activated immediately after a trauma, and have been recognised as one of the key mediators of neuroinflammation in the acute phase of SCI 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Neuroinflammation and oxidative stress (OS) following SCI trigger secondary neuropathies such as glial accumulation, neuronal loss, and demyelination that exacerbate neurological dysfunction and functional disorder. 3 , 4 , 5 Microglia are the resident immune cell of the central nervous system and become activated immediately after a trauma, and have been recognised as one of the key mediators of neuroinflammation in the acute phase of SCI. 6 , 7 Moreover, microglia actively produce multiple oxidisers including nitric oxide (NO) and reactive oxygen species (ROS) that contribute to neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%